Analysis of Application Success in XYZ Agency as an Online Learning Media Using the Delone and Mclean Models - Erika Noor Dianti; Endang Sugiharti (Journal of Advances in Information Systems and Technology, 2023)
Internet users in Indonesia have shown a rapid increase. This indicates that the development of information and communication technology is growing, bringing many life changes, thus demanding the education industry to strive to improve the quality of education continuously. However, at the beginning of 2019, COVID-19 pandemic emerged, which required that all students not be allowed to do face-to-face learning. Because of this problem, companies are starting to create online learning technologies that have a positive impact. In 2022, XYZ application is a learning application ranked 9th among the most popular applications. Nevertheless, in its use, there are still obstacles. Based on this description, this study will analyze application's success using Delone and Mclean models to determine whether application has been considered successful. The research data was obtained by distributing questionnaires online with a total of 240 respondents who were users who had used e-learning in XYZ agency with an age range of 15 to 45 years. This study used quantitative methods and data processing using Smart PLS version 4 software to test inner and outer models. The results showed that success rate of e-learning in XYZ agency was very high, and out of twelve hypotheses, eight were accepted, and four were rejected. The factors that support success of e-learning in XYZ agency are seen from accepted hypotheses. At the same time, factors that hinder application's success are information quality, system quality, service quality, instructor quality, and user satisfaction. From these inhibiting factors, appropriate recommendations are then given. The results of this research are expected to be considered by e-learning in XYZ agency developers and providers